PARTISIPASI POLITIK PEMILIH PEMULA DALAM PEMILIHAN LEGISLATIF TAHUN 2014 (Studi Pada Masyarakat Adat di Kelurahan Kulaba Kecamatan Pulau Ternate) - Hamis Basahona; Syahril Muhammad (Universitas Khairun, 2018)
This research is a study of the political participation of new voters in the 2014 legislative elections. The study of indigenous peoples is motivated by the use of local cultural symbols namely